Perilaku Petani Milenial Provinsi Jawa Barat dalam Penerapan Climate-Smart Agriculture (CSA) pada Tanaman Hortikultura - Triya Ayu Retnaningtyas; Dwiningtyas Padmaningrum; Sapja Anantanyu (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Millennial farmers become superior and competitive human resources as determinants of the progress of agricultural development. Millennial farmers must be adaptive to digitalization technology and innovation and environmentally friendly cultivation techniques to face agricultural development, including climate change challenges. Climate-smart agriculture (CSA) behavior is the strategic effort of millennial farmers as an approach to dealing with the impacts of climate change on the agricultural sector, as well as efforts by the agricultural industry to reduce its impact on climate change through efficient management of crops, land and soil, and water. The management is based on three pillars of CSA: 1) Increasing agricultural productivity and income, 2) Improving adaptation and resilience to climate change, and 3) Reducing greenhouse gas emissions. This study aims to analyze CSA implementation behavior based on the Theory of Planned Behavior (TPB) by examining the direct and indirect effects of attitude variables, subjective norms, perceived behavioral control, and intentions. These variables are measured by integrating TPB with the CSA context. The research sample was 198 respondents of Millennial Farmer Ambassadors and Andalan Farmer Ambassadors in West Java Province, conducted in 2023. This research uses a quantitative approach with the Structural Equation Model-Partial Least Square (SEM-PLS) method to analyze complex models with many variables—data collection techniques using questionnaire instruments that have been valid and reliable. The results showed that attitude, perceived behavioral control, and intention significantly influence behavior both directly and indirectly through intention (p-value < α 0.05). Meanwhile, subjective norms do not substantially affect behavior directly or indirectly through intention (p-value > α 0.05). So, it is necessary to develop interventions that strengthen the formation of positive intentions and the need for practical support for subjective norms related to CSA implementation behavior in millennial farmers.